2003
DOI: 10.1002/app.11598
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conduction and dielectric properties of poly(methyl methacrylate)/perylene solar concentrators

Abstract: Poly(methyl methacrylate) doped with fluorescent perylene dye was prepared by both radical polymerization of methyl methacrylate and solvent casting from polymer solutions. The samples were characterized by differential scanning calorimetry, Fourier transform infrared spectroscopy, electrical conductivity, and dielectric properties. Both conductivity and dielectric properties were measured in the temperature range 303-433 K and the frequency range 10 3 to 5 ϫ 10 6 Hz. The results show that the directcurrent el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…6 shows the directly measured hourly values of g opt for all the investigated BFSCs. One notices for b > 160°t hat g opt increases near both sunrise and sunset and gets lower at midday in agreement with our published work [3]. On the other hand, for b 6 160°the behavior is quite different; the value of g opt reaches a stationary value for as long as 7 h around midday and records lower values at both sunrise and sunset.…”
Section: Enhancement Of the Optical Efficiency By Bfscssupporting
confidence: 85%
See 2 more Smart Citations
“…6 shows the directly measured hourly values of g opt for all the investigated BFSCs. One notices for b > 160°t hat g opt increases near both sunrise and sunset and gets lower at midday in agreement with our published work [3]. On the other hand, for b 6 160°the behavior is quite different; the value of g opt reaches a stationary value for as long as 7 h around midday and records lower values at both sunrise and sunset.…”
Section: Enhancement Of the Optical Efficiency By Bfscssupporting
confidence: 85%
“…It is clearly illustrated that the ratio J sc /J rc reaches a value of 7 during more than 6 h around midday for an apex angle of 150°, corroborating the large light concentration effect achieved by the BFSCs. It is also observed that the ratio J sc /J rc exceeds this value near sunrise and sunset; from the practical point of view this behavior is advantageous, since better utilization of the FSC is achieved as both the direct solar radiation component and the sensitivity of PV cell decreases [3]. Fig.…”
Section: Enhancement Of the Optical Efficiency By Bfscsmentioning
confidence: 89%
See 1 more Smart Citation
“…This can be understood according to the presence of the ester functional group, with the carbonyl oxygen atom being a basic site, leads to PMMA exhibiting electrondonor ability. So, PMMA is described as a basic polymer containing an electron-donor atom [16]. Hence, the polarization process occurs by electron jumping (hopping and/or tunneling) between donor atoms and empty sites located in the energy band gap.…”
Section: Frequency Dependence Of the Dielectric Propertiesmentioning
confidence: 99%
“…The physical properties of PMMA have led to its extensive use in outdoor electrical applications [6][7][8][9]. According to the published literature, it was found that its optical properties have been extensively studied [5,10] while its electrical properties still need much more research.…”
Section: Introductionmentioning
confidence: 99%